Transformation During Transitions: Intentionality in Simulation-Based Education for Professional Identity Development - Kerins, Joanne; Somerville, Susan G; Tallentire, Victoria R (Simulation in healthcare : journal of the Society for Medical Simulation, 2025)
There is growing evidence that simulation-based education can contribute to professional identity development. This commentary discusses the potential theoretical underpinning of this process and considers the role of simulation debriefing to support significant periods of transition in professional identity. Transformative learning theory has been described as a theoretical basis for professional identity development in the context of simulation-based education, but the concepts of liminality, identity work, and narrative reflection are less well explored. These additional concepts offer more nuanced ways of understanding professional identity development during transitions and provide further theoretical underpinning for supportive interventions. This commentary provides simulation-based education strategies to support professional identity development during transitions that could be used as fruitful springboards for educational interventions and further research.